PERSPEKTIF TENAGA PENGAJAR TERHADAP ANAK YANG BERKEBUTUHAN KHUSUS DI SDN 39 CAKKE DAN SDN 157 CAKKE KELURAHAN LAKAWAN KECAMATAN ANGGERAJA - Sukriadi HR; Mahmud Irawan; Rifki Alwi; E.M. Usran (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
Children with special needs are children who have limitations in cognitive, physical, or emotional functions that hinder their development. Children with special needs can also be interpreted as children who need special services to be able to carry out daily activities properly. This includes children who experience problems and who have advantages related to growth and development related to intelligence, senses, and limbs. So children with special needs should be included in schools that are indeed special for the child. Therefore, it is necessary to conduct research on what is happening in the field regarding public schools that accept children with special needs. the reason why public schools are based on the law so that children with special needs are admitted to public schools; Article 32 paragraph 2 of the law, that every citizen has the right to a proper education, as we know that children who need The efforts of teaching staff to educate children with special needs are very diverse and of course in accordance with the challenges faced, as well as the general school policy in assessing children with special needs, because in fact children who are studying always expect assessment.